1978
DOI: 10.1111/j.1532-5415.1978.tb03326.x
|View full text |Cite
|
Sign up to set email alerts
|

Senile‐Presenile Dementia: Follow‐Up Data on an Effective Psychotherapy‐Anticoagulant Regimen*

Abstract: This report contains follow-up data on the effects of an anticoagulant-psychotherapy regimen in presenile and senile dementia. Over a two-year period, 49 such patients who were seriously ill were treated with a Coumadin-psychotherapy regimen; 34 (69 percent) improved (4 of them dramatically) and 15 (31 percent) did not improve or became worse. The underlying pathologic processes are discussed, with the rationale for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…This phenomenon has also been reported by Ahn and coworkers who showed that fibrin clots formed in the presence of Aβ have an abnormal structure, making them resistant to degradation [61]. In addition, anticoagulant treatment improves cognition in mouse models and of AD and dementia patients [29,[62][63][64]. However, anticoagulant therapy might cause severe problems in elderly patients having a fragile vasculature increasing the risk of systemic bleeding.…”
Section: Discussionsupporting
confidence: 69%
“…This phenomenon has also been reported by Ahn and coworkers who showed that fibrin clots formed in the presence of Aβ have an abnormal structure, making them resistant to degradation [61]. In addition, anticoagulant treatment improves cognition in mouse models and of AD and dementia patients [29,[62][63][64]. However, anticoagulant therapy might cause severe problems in elderly patients having a fragile vasculature increasing the risk of systemic bleeding.…”
Section: Discussionsupporting
confidence: 69%
“…Additional evidence supporting an important role for fibrin(ogen) and clot formation in AD are the positive results obtained with anticoagulant therapy for this disease (Ratner et al, 1972; Walsh et al, 1978). Although those studies were small, the anticoagulant treatment either stopped the deterioration or provoked an improvement of the disease (Walsh, 1996).…”
Section: Discussionmentioning
confidence: 89%
“…In human studies, placebo-treated dementia patients showed a significant deterioration in cognition, while warfarin-treated patients did not show any change in cognitive decline [46]. In addition, unregulated studies carried out several decades ago showed that the majority of dementia patients treated with warfarin presented with improved cognition compared to untreated patients [47, 48]. Furthermore, an epidemiological study on atrial fibrillation patients showed that long-term warfarin treatment is protective against dementia [49].…”
Section: Thrombotic/fibrinolytic System In Admentioning
confidence: 99%